Rare PHEX variant with insidious presentation leads to a delayed diagnosis of X-linked hypophosphatemia - Constantacos, Cathrine (BMJ Case Rep, 2021)
A 7-year-old girl without a significant previous medical history was diagnosed with X-linked hypophosphatemic rickets (XLHR) due to a rare, most likely pathogenic, PHEX gene variant after a 4-year delayed diagnosis due to mild clinical presentation. At 2 years of age, her intoeing and femoral bowing were attributed to physiologic bowing and borderline vitamin D sufficiency, despite phosphorus not being measured. Hypophosphatemia was eventually detected after incomplete improvement of bowing and leg length discrepancy with suboptimal linear growth. This rare PHEX variant (c.1949T>C, p.Leu650Pro) further supported the clinical diagnosis of XLHR. Treatment with burosumab (an anti-FGF23 monoclonal antibody) normalised phosphorus and alkaline phosphatase levels and improved her bowing. The diverse phenotypic presentation of this variant can result in delayed diagnosis and highlights the importance of prompt assessment of phosphorus levels in patients with skeletal deformities to ensure timely recognition and treatment.